2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6883992
|View full text |Cite
|
Sign up to set email alerts
|

Interactive crowdsourcing to spontaneous reporting of Adverse Drug Reactions

Abstract: Adverse Drug Reactions (ADRs) has become a worldwide problem that draws the attention of people from all racial and ethnic groups. The number of deaths caused by ADRs has greatly increased and led to many drug withdrawals in the last decades. Recent research findings indicate that most ADRs can be effectively prevented to some extent by using computeraided information technologies. Though many spontaneous reporting systems (SRSs) have been built to enhance the pharmacovigilance, the ADRs data is still very spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The use of crowdsourcing has been discussed in pharmacovigilance, but this has been in the context of collecting adverse event reports and for subsequent signal detection. An example is reported by Chen et al [12]. We have developed a tool and, through a small focussed proof-ofconcept study, shown its usability in terms of data link upload and subsequent search function.…”
Section: Crowdsourcing: a Promising Tool In Pharmacovigilance Teachingmentioning
confidence: 99%
“…The use of crowdsourcing has been discussed in pharmacovigilance, but this has been in the context of collecting adverse event reports and for subsequent signal detection. An example is reported by Chen et al [12]. We have developed a tool and, through a small focussed proof-ofconcept study, shown its usability in terms of data link upload and subsequent search function.…”
Section: Crowdsourcing: a Promising Tool In Pharmacovigilance Teachingmentioning
confidence: 99%
“…Many MCS applications have been developed and are used for environment monitoring [2,4], infrastructure monitoring [3,10,11], qualityof-experience analysis [8,9], surface perception [5], and public safety [7]. In parallel to MCS applications, there are some studies aiming at improving the energy-efficiency in MCS [32,33].…”
Section: Introductionmentioning
confidence: 99%